Pengaruh Penggunaan Jakcard terhadap Putusan Kunjungan Taman Margasatwa Ragunan di Jakarta - Muhammad Dzakir Alif; Endah Widati; Hamzah Robbani (FOCUS, 2020)
The purpose of this study was to determine whether or not the use of jakcard had an effect on the decision to visit the Ragunan Wildlife Park in Jakarta. The research method used in this paper is a causal associative method with a quantitative approach. Data collection techniques used are questionnaires, interviews and observations. The number of respondents is taken based on people who have an active JakCard card and have visited TMR at least 1 time as many as 100 people. Based on the results of the study, it was found that there was an effect of using a jakcard on the decision to visit the Ragunan Wildlife Park in Jakarta with a coefficient of determination of 42.92% and the remaining 58.08% determined by the contribution of other factors not examined in this study.